Knowledge analysis of construction professionals about the civil construction and demolition waste in the city of Campo Mourão – PR - Aragão, Franciely Velozo; Aragão, Emanuely Velozo; Kurta, Valdomiro Lubachevski; Madeiros Filho, Dante Alves; Santos Neto, João Batista Sarmento do; Sousa, Larissa de; Cotrin, Syntia Lemos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The construction industry is responsible for generating a large volume of solid waste from construction and demolition, which pose a serious problem in many Brazilian cities, mainly due to irregular disposal of these residues. Even with the existence of rules and laws that establish guidelines for waste management from construction and demolition, there is still an inefficiency of decision making regarding the proper management of such waste. This study aims to analyze the knowledge rate of construction professionals, regarding the management of waste from construction and demolition from a case study in Campo Mourao-PR. For data collection, it was developed and implemented a structured questionnaire to 53 professionals, civil engineers and architects, registered in the Regional Association of Engineers and Architects of Campo Mourao - AREA. In the study it was observed that despite having knowledge of the law involving waste management of construction, it is necessary that these professionals have education and information about waste minimization and recycling, as well as investments and oversight to prevent irregular disposal leading environmental impact.